Day-ahead distributed coordination scheduling strategy considering flexible resources mutual aid among regional grid - LI Huibin; LIU Xiangyu; GU Xueping; SHI Shanzhe (Diance yu yibiao)
In order to adapt to the regional operation of power system, and the uneven regional distribution of multi-type flexibility resources, a distributed and coordinated dispatching strategy considering the mutual aid of multi-area and multi-type flexible resources is proposed. The flexible supply model of thermal power units, energy storage and interruptible load is established, and the flexibility demand caused by the uncertainty of both source and load is analyzed. The risk cost of insufficient regional flexibility is quantified by conditional value-at-risk. Based on improved alternating direction method of multipliers (ADMM), the mutual aid level of inter regional flexibility is analyzed considering multi-region and multi-type flexible resource mutual aid and flexible mutual aid service cost, so as to realize the cross regional coordination as well as interaction of multi-type flexible resources under decentralized scheduling. The case verification results show that the strategy promotes the flexible supply-demand balance of large power grid, reduces system operation cost and the risk of abandoning new energy and shedding load, which is of positive significance to economic and safe dispatching.